Preparing a National Transport Strategy : Suggestions for Government Agencies in Developing Countries - Lee, John; Hine, John L. (World Bank, Washington, DC, 2014)
The purpose of this report is to assist policy makers and planners in developing countries in the preparation of a National Transport Strategy (NTS). The report highlights lessons that can be learned from NTSs developed by different countries around the world. It draws upon transport strategy and policy documents from 23 countries and from a range of World Bank source material. The aim is not to provide a ready-made strategy document but to identify relevant questions and choices that need to be considered in preparing an NTS. At each stage of the development of the NTS, a checklist of considerations is given, and, where appropriate, examples of good and bad practice are identified. Within the report particular attention is paid to separately identifying Objectives, Policy Principles and Strategies. Objectives express society's goals, which should reflect the general socio-economic goals of the country-goals that are shared with other (non-transport) sectors. Policy Principles represent the principles that should govern the pursuit of those goals. They are the guiding philosophy for decisions within the sector. Strategies represent the ways in which goals are to be achieved in line with the policy principles. A wide range of policies relating to the sector as a whole and to different modes of transport are considered in the report, covering topics such as investment planning, private provision of road infrastructure, transport services, rail infrastructure and operations, ports and multi-modal transport, route service franchising, pricing, cost recovery and taxation. In addition, a series of examples of how strategies can be formulated based on objectives and policy principles are given. Throughout the report, consultation and transparency in the preparation of an NTS are stressed. The report concludes with a broad assessment of the strengths and weaknesses of NTSs reviewed for the report.